PREFERENSI KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN MOCHI LAMPION BERDASARKAN VARIAN RASA DAN KEMASAN (Suatu Kasus pada Konsumen di Toko Mochi Lampion Kecamatan Cikole, Kota Sukabumi) - Anni Sugihhartati; Maman Haeruman; Dety Sukmawati; Euis Dasipah; Nataliningsih Nataliningsih; Agi Dahtiar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The purpose of this study was to analyze the effect of variations in taste and packaging on purchasing decisions for Mochi Lantern cakes. The method used in this study is a quantitative method with descriptive analysis. Data collection was carried out using direct interview methods from respondents who were in the field using a questionnaire. Attributes observed in this study were flavor variants and types of packaging. The questionnaire proposed was first tested using validity and reliability tests. Descriptive analysis of respondents' characteristics and consumption behavior, preference for Mochi Lantern products such as flavor variants and types of packaging, as well as characteristics of Mochi Lantern products, these are taken into account when consumers make purchasing decisions and are analyzed using path analysis. The results showed that the flavor variant had a positive and significant indirect effect on the purchasing decision of Mochi Lanterns in the city of Sukabumi. Flavor variants indirectly have a positive effect on purchasing decisions through packaging variables, and have a direct positive effect on purchasing decisions on taste diversification. The more and higher the buyer's decision to purchase flavor variants, the greater the packaging variable in purchasing Mochi Lanterns in Sukabumi City.